2000
DOI: 10.2136/sssaj2000.64175x
|View full text |Cite
|
Sign up to set email alerts
|

Tracer vs. Pressure Wave Velocities through Unsaturated Saprolite

Abstract: breakthrough curves are often used to estimate model parameters, including effective porosity, finger width, Saprolite is a form of weathered bedrock that is commonly used as mobile zone porosity, and the retardation factor. Each the host material at waste disposal sites in the Southeastern Piedmont. However, estimating the unsaturated hydraulic and transport proper-approach provides valuable information about the beties of saprolite is difficult due to saprolite's low permeability. We havior of solute transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 46 publications
4
70
0
Order By: Relevance
“…For higher values of hydraulic Peclet number the flow wave velocities dominate yielding a value consistent with the kinematic theory (advection of the flow wave). This is coherent with the experiments carried out by Rasmussen et al (2000) who put forward evidence for diffusion-dominated soil water pressure waves whose velocities initially exceeded kinematic wave celerities in the more shallow depths of intact saprolite columns. Subsequently, diffusion-dominated soil water pressure wave velocities decreased with depth, conforming with kinematic wave theory.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…For higher values of hydraulic Peclet number the flow wave velocities dominate yielding a value consistent with the kinematic theory (advection of the flow wave). This is coherent with the experiments carried out by Rasmussen et al (2000) who put forward evidence for diffusion-dominated soil water pressure waves whose velocities initially exceeded kinematic wave celerities in the more shallow depths of intact saprolite columns. Subsequently, diffusion-dominated soil water pressure wave velocities decreased with depth, conforming with kinematic wave theory.…”
Section: Resultssupporting
confidence: 88%
“…The SRM approach accounts also for the capability of fractures to store the percolating water partially on their facial micro -concavities that creates conditions suitable for the water and contaminants to get exchanged between the two domains (Nimmo and Malek-Mohammadi, 2015;Price et al, 2000). An alternative conceptual model uses kinematic theory to predict the pressure wave velocity, or celerity, of unsaturated media (Rasmussen et al, 2000). This formulation assumes that rapid hydraulic responses occur due to semi -compressible flow within the rock matrix.…”
Section: Conceptual Models Of Infiltration In Unsaturated Chalkmentioning
confidence: 99%
“…As a result of the effective porosity in Hillvi, mass remains longer in the unsaturated and saturated stores of each grid cell, because a fraction (1 − * n eff ) of these stores (immobile soil water) does not take part in the transport process. While a simplification, because it, for example, ignores exchange between the mobile and immobile domain, this parameter represents a dual porosity system (e.g., Buttle and Sami, 1990;Corapcioglu and Wang, 1999;Stephens et al, 1998;Rasmussen et al, 2000) with a mobile and immobile water domain and the calibration result for this parameter suggests that the mixing volume of deuterium was controlled by an immobile soil water fraction. A dual porosity system is consistent with the study of Brooks et al (2010) in the same small watershed: based on water-isotope data, they found soil water that is tightly bound (immobile) within small soil pores remains in the soil or leaves the soil through transpiration by trees, but it does not contribute to matrix flow and is disconnected from mobile or stream water.…”
Section: Process Understanding Through the Hillvi Modelmentioning
confidence: 99%
“…Following recommencement of irrigation, Jackson et al (2016) observed during their multi-tracer hillslope irrigation experiment a fast trench flow and piezometer response indicating a pressure wave celerity much faster than observed dye tracer velocities. Rasmussen et al (2000) presented parametric expressions for the celerity, which predicted pressure wave travel times 2 to 15 times faster than the tracer velocity for their short-duration fluid irrigation experiments with intact saprolite columns. How the perturbation (irrigation) was exactly transmitted through the flow domain at our site remains unclear.…”
Section: Celerities and Velocities At The Hillslope Scalementioning
confidence: 99%
“…While pressure wave translatory flow was proposed back in the early 1960s by Hewlett and Hibbert (1967) as part of the Variable Source Area concept, recent papers have rejuvenated interest in this area (Rasmussen et al, 2000). Torres et al (1998) found that 'a pressure head signal advanced through the soil profile on average 15 times greater than the estimated water and wetting front velocities.…”
Section: Pressure Wave Translatory Flowmentioning
confidence: 99%